Constrained Peptides as Miniature Protein Structures. (26th September 2012) - Yin, Hang
Abstract : This paper discusses the recent developments of protein engineering using both covalent and noncovalent bonds to constrain peptides, forcing them into designed protein secondary structures. These constrained peptides subsequently can be used as peptidomimetics for biological functions such as regulations of protein-protein interactions.